Air pollution during the winter period and respiratory tract microbial imbalance in a healthy young population in Northeastern China. (March 2019) - Li, Xinming; Sun, Ye; An, Yunhe; Wang, Ran; Lin, Hong; Liu, Min; Li, Shuyin; Ma, Mingyue; Xiao, Chunling
Abstract: In order to investigate the relationship between air pollution and the respiratory tract microbiota, 114 healthy volunteers aged 18–21 years were selected during the winter heating period in Northeast China; 35 from a lightly polluted region (group A), 40 from a moderately polluted region (group B) and 39 from a heavily polluted region (group C). Microbial genome DNA was extracted from throat swab samples to study the oral flora composition of the volunteers by amplifying and sequencing the V3 regions of prokaryotic 16S rRNA. Lung function tests were also performed. The relative abundance of Bacteroidetes and Fusobacteria were significantly lower and Firmicutes Proteonacteria and Actinobacteria higher in participants from polluted regions. Within bacteria classes, Bacterioida abundance was lower and Clostridia abundance higher in polluted areas, which was also reflected in the order of abundance. In samples from region C, the abundance of Prevotellaceae, Veillonellaceae, Porphyromonadaceae, Fusobacteriaceae Paraprevollaceae and Flavobacteriaceae were lowest among the 3 regions studied, whereas the abundance of Lachnospiraceae and Ruminococcaceae were the highest. From group A to group C, the relative class abundances of Prevotella, Veillonella, Fusobacterium, Camphylobacter and Capnocytophaga Porphyromonas, Peptostreptococcus and Moraxella became lower in polluted areas. Pulmonary function correlated with air pollution and the oropharyngeal microbiota differed within regions of high, medium and low air pollution. Thus, during the winter heating period in Northeast China, the imbalance of the oropharyngeal microbiota might be caused by air pollution and is likely associated with impairment of lung function in young people. Graphical abstract: Image 1 Highlights: There were different air pollutions in 3 areas of Northeast China. The oropharyngeal microbiota differed according to the air pollution. Pulmonary function had a declining trend in moderately- and heavily-polluted areas. Oropharyngeal microbiotic imbalance by air pollution might cause lung impairment. Abstract : The oropharyngeal microbiota in healthy participants differed according to the extent of air pollution in 3 regions of Northeastern China.